Mulieres novarum rerum cupidae. The Rooting of Priscillianism among Women - Olivares Guillem, Andrés (Gerión. Revista de Historia Antigua, 2021)
One of the accusations made in Trier’s trials against bishop Priscillian of Avila was about holding evening meetings with women who followed him in a herd, avid for novelties. A stereotype image, which was used by antipriscillianist literature linked to the description of many heretics, lies behind this accusation. Besides, the reference of a woman among Priscillian’s teachers had a great impact on the heretical character of the priscillianist movement. This pejorative image differs from the well-known examples of women who followed Priscillian. They were cultivated women belonging to the Hispanic and Aquitanian aristocracy. Far from being heterodox, meeting with women for reading biblical texts is similar to some ascetic practices among the ladies of the late Roman aristocracy.
Keywords: Female Asceticism; Urbica; Euchrotia; Procula; Galla; Severa; Agape